2021
DOI: 10.1016/j.jtho.2021.01.268
|View full text |Cite
|
Sign up to set email alerts
|

MA13.07 Structural Classification of Atypical EGFR Mutations Identifies 4 Major Subgroups with Distinct Patterns of Drug Sensitivity

Abstract: March 2021Abstracts S183osimertinib. These findings define subgroups of EGFR mutations that may better guide future treatment approaches for atypical EGFR mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Interestingly, both E709X and L747X have been identified as pocket volume reducing (PVR) mutations that are predicted to be more sensitive to second-generation EGFR TKIs than firstor third-generation agents (10). We also assessed the activity of afatinib against mutations that have been implicated in the acquired resistance to osimertinib, including G724S (n = 13), L718X (n = 5) and C797S (n = 1), all of which have been identified as PVR mutations (10). G724S mutations showed some sensitivity towards afatinib with an ORR of 17% and DCR of 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, both E709X and L747X have been identified as pocket volume reducing (PVR) mutations that are predicted to be more sensitive to second-generation EGFR TKIs than firstor third-generation agents (10). We also assessed the activity of afatinib against mutations that have been implicated in the acquired resistance to osimertinib, including G724S (n = 13), L718X (n = 5) and C797S (n = 1), all of which have been identified as PVR mutations (10). G724S mutations showed some sensitivity towards afatinib with an ORR of 17% and DCR of 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Using the data from patients with NSCLC, cell lines, and computer models, Jacquulyne Robichaux et al. found that EGFR mutations can be divided into four functional subgroups including classcical-like mutation, T790M-like mutations, exon 20 insertions and pocket volume reducing (PVR) mutation (interior of the ATP binding pocket or in α-helix/P-loop) ( 8 ). The mechanisms of resistance to third-generation EGFR TKIs have been demonstrated in recent years.…”
Section: Discussionmentioning
confidence: 99%